«Linguista sum… sed linguam non definio». Absence de définition de la langue et circularité de la construction structurale. (Remarques sur la classification jakobsonienne des aphasies) - Toutain, Anne-Gaëlle (Rivista Italiana di Filosofia del Linguaggio, 2014)
This article analyzes the Jakobsonian classification of aphasias. It aims to show on the one hand the non-linguistic character of this classification and on the other hand its asymmetry, in spite of the fact that its author had conceived his structural construction as symmetrical. The non-linguistic character of Jakobson’s formulation is due to the absence of any definition of language, this absence being the main characteristic of Jakobsonian linguistics: concerning the aphasia problem, the Jakobsonian formulation is linguistic solely by virtue of its object, aphasia, which is already considered as a linguistic concern because it belongs to the field of « language », but which is not defined as such (as linguistic). As for asymmetry, it demonstrates first the circularity of the Jakobsonian representation of language (the duality between structure and functioning), and secondly the non-linguistic character – in the Saussurean sense of the term – of the aphasia problem. Thus it appears that breaking (in the sense of Gaston Bachelard) with idiom is the prerequisite of a scientific apprehension of language, and therefore of any interdisciplinarity, this being one of Jakobson’s favorite topics but one that this linguist failed to render fruitful because he did not offer a real definition of language.